POLITIK ANGGARAN PROVINSI JAWA TENGAH : ANALISIS REALISASI APBD PROVINSI JAWA TENGAH TAHUN ANGGARAN 2008-2010 - Agus Riyanto (Universitas Wahid Hasyim Semarang, 2012)
Abstract The local Budget revenue and expenditure or APBD is annual financial plan that made by local government with local parliament (DPRD), which is describes activate and program plan to achieve the local medium development plan (RPJMD). The or APBD should be optimized to achieve the public welfare which is the purpose of the local government. This article will analyze the realization of the local budget of central java in 2008 until 2010. The research problem is “how the budget realization in the Local revenue and expenditure budget (APBD) of the Province of Central Java in 2008 until 2010? Key words : Local budget or APBD, apparatus expenditure, public expenditure, Local Medium Development Plan (RPJMD), Vision and Mission.